IMPLEMENTATION OF PEER LESSONS LEARNING STRATEGIES TO IMPROVE ISLAMIC RELIGIOUS EDUCATION LEARNING OUTCOMES FOR NINTH-GRADE STUDENTS D AT SMPN 4 TAMBANG KAMPAR - Husnidar Husnidar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper is based on the students’ low learning outcomes of Islamic Religious Education at Class IX.D of SMPN 4 Tambang. The purpose of the classroom action research is to describe whether the application of Peer Lessons learning strategies can improve students’ learning outcomes of Islamic Religious Education at class IX.D of SMPN 4 Tambang on the subject of Fiqh or not, which was conducted for one month. The research subjects involved 30 Class IX.D students at SMPN 4 Tambang. The type of research was classroom action research. The research instrument consisted of learning achievement tests and data collection instruments, which were teacher and student activities observation sheets. Based on the discussion and analysis results as presented previously, it can be concluded that the Peer Lessons learning strategy could improve students’ learning outcomes on the Fiqh learning at Class IX.D of SMPN 4 Tambang. In the pre-cycle, the average was 66.3. The average score of students’ learning outcomes in cycle I increased to 72.3. In addition, in cycle II there was also an improvement with an average score of 79.5 in the good category. It proves that the Peer Lessons learning strategy can improve students’ learning outcomes at class IX.D of SMPN 4 Tambang.